2016
DOI: 10.1002/adfm.201601328
|View full text |Cite
|
Sign up to set email alerts
|

“To Catch or Not to Catch”: Microcapsule‐Based Sandwich Assay for Detection of Proteins and Nucleic Acids

Abstract: The development of new assays that specifically detect intermediate or final products of biotechnological processes or multiple analytes in biomedical research is important for diagnostics and biotechnology. This study presents a microcapsule‐based sandwich assay for detection of proteins and nucleic acids using flow cytometry as an optical readout. The main component of the assay are robust chemically cross‐linked microcapsules that are coated with adaptor proteins such as protein A or streptavidin. In the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 65 publications
0
45
0
Order By: Relevance
“…We then tested both microcapsules and PS beads in a sandwich immunoassay for the protein analyte, human beta-2 microglobulin (hβ 2 m), which is measured in the plasma to detect cancer and in the urine to detect renal failure [ 26 ]. In this assay, the BBM.1 antibody on microcapsules or PS beads binds hβ 2 m, which is then detected with polyclonal rabbit anti-hβ 2 m antibody, followed by fluorescently labeled anti-rabbit secondary antibody ( Fig 2C ) [ 9 ]. A dose-response study comparing the microcapsules and the PS beads showed clearly that the microcapsules detected hβ 2 m with much higher sensitivity than the PS beads ( Fig 2D ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We then tested both microcapsules and PS beads in a sandwich immunoassay for the protein analyte, human beta-2 microglobulin (hβ 2 m), which is measured in the plasma to detect cancer and in the urine to detect renal failure [ 26 ]. In this assay, the BBM.1 antibody on microcapsules or PS beads binds hβ 2 m, which is then detected with polyclonal rabbit anti-hβ 2 m antibody, followed by fluorescently labeled anti-rabbit secondary antibody ( Fig 2C ) [ 9 ]. A dose-response study comparing the microcapsules and the PS beads showed clearly that the microcapsules detected hβ 2 m with much higher sensitivity than the PS beads ( Fig 2D ).…”
Section: Resultsmentioning
confidence: 99%
“…Core-shell particles were prepared, crosslinked, and surface-modified with protein A as described in section 2.2 and 2.3 [ 9 ]. High-binding 96-well black well plates were coated with 100 μg mL -1 protein A in carbonate buffer (pH 9.6) overnight at 4°C and then blocked with 1% (w/v) BSA overnight.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations